U.S. Army tactics field manual (Lyons Press, an imprint of Globe Pequot Press, 2013)
Tactics is the art and science of employing all available means to win battles and engagements. Specifically, it comprises the actions taken by a commander to arrange units and activities in relation to each other and the enemy. Filled with diagrams of attack plans, defensive strategies, and troop movements, U.S. Army Tactics Field Manual is the playbook the U.S. Army uses to employ available means to win in combat. This book provides combat-tested concepts and ideas modified to exploit emerging Army and joint capabilities. This book focuses on the organization of forces, minimum essential control measures, and general planning, preparation, and execution considerations for each type and form of combat operation. It is the common reference for all students of the tactical art, both in the field and the Army school system.